(untitled) (REMUNOM, 2024)
Alzheimer’s disease is a progressive neurodegenerative condition affecting cognition, functionality, and behavior, primarily impacting the elderly population. It is an incurable disease; however, if diagnosed and treated early, it can alleviate and delay its symptoms. The impacts of the disease affect the following areas: Cognitive: memory, reasoning, attention, and problem-solving; Emotional: mood changes, depression, anxiety, frustration, agitation, disorientation, insecurity, leading to a negative impact on self-esteem; Functional: inability to perform daily activities; and Organic: loss of motor function, mobility, and coordination. Understanding the specific aspects influencing cognition in long-term care institutions is crucial. This is an exploratory and descriptive study with a quantitative-qualitative approach. Data collection occurred in person through the Beck Inventory, Clinical Functional Vulnerability Index, and daily food consumption tests. The study involved 23 elderly participants, of both genders, residing in the institution. Beck inventories revealed that the degree of anxiety was associated with the elderly person’s contact with family and the time spent outside the institution, while depression was linked to comorbidities and the reason for institutionalization. Regarding functionality, 47% of the elderly were robust, but the sum of the frail and potentially frail elderly individuals accounted for 52%, representing the majority of the elderly population. Regarding daily food consumption, approximately 54% of the participants had more than 4 meals a day, and 81% reported having set meal times. Additionally, 63% consumed fruits, vegetables, and greens, and 48% consumed milk and dairy products. Open-ended questions generated three categories: the importance of food in a long-term care institution; food as a source of love, emptiness, smiles, and soul; and reflections on emotional and spiritual aspects. Functional, emotional, and organic changes affect cognition in Alzheimer’s disease, and occupational therapy is essential as it aims to improve the elderly person’s quality of life through constant adaptation and stimulation.